ANALISIS DESKRIPTIF HUBUNGAN INFLASI DAN PENANAMAN MODAL ASING (PMA) DI INDONESIA TAHUN 2016-2023 - Salfiah Salfiah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Inflation is defined as a general and sustained increase in the prices of goods and services over a certain period, which can affect the attractiveness of foreign investment. This study aims to analyze the relationship between inflation and Foreign Direct Investment (FDI) in Indonesia during the 2016–2023 period. Using a descriptive quantitative method and simple linear regression analysis, the results show that inflation has a negative and significant effect on FDI, as indicated by a t-test value of -4.517 with a significance of 0.000. Conversely, FDI also has a positive and significant effect on inflation, with a coefficient of 0.012 and a significance of 0.039. These findings indicate a reciprocal relationship, where high inflation reduces FDI, while an increase in FDI may potentially drive inflation. Therefore, maintaining price stability is key to creating a conducive investment climate and supporting long-term economic growth in Indonesia.